Greenhouse gas emissions in China’s national Parks: A 2020 National-Scale analysis and Implications for management - Shenglan Yang; Huan Xu; Zhicong Zhao; Fangyi Wang; Qiaoyun Sun; Jiale Tang; Jia He; Le Zhong (Ecological Indicators)
National parks serve as crucial carbon reservoirs and sinks, yet their capacity to mitigate carbon emissions faces significant challenges, highlighting the urgent need for robust greenhouse gas (GHG) control and reduction strategies. Existing studies have often lacked comprehensive, spatially detailed GHG emission inventories for national parks at a national scale, hindering targeted carbon management efforts. This study addresses this gap by conducting a uniform national-scale assessment of GHG emissions across China’s five national parks in 2020, with a focus on spatial distribution and emission source characterization. Our findings reveal that these parks collectively emitted 6.79 million tonnes of GHGs, primarily carbon dioxide, with residential and animal husbandry activities being the dominant sources. Emission patterns displayed strong spatial coherence, with high-emission and low-emission areas clustering distinctly. Although most national parks exhibited per-unit area emissions below the national average, hotspots in the Three-River-Source National Park exceeded the national average by 1.78 times. This study underscores the critical role of emission mapping in formulating effective GHG mitigation strategies to bolster the carbon–neutral potential of national parks.